Postharvest changes in beans during prolonged storage in contrast to accelerated aging - Jacinto Hernández, Carmen; Bernal-Lugo, Irma; Garza-García, Ramón; Garza García, Dagoberto (Revista Mexicana de Ciencias Agrícolas, 2017)
The decrease in the commercial value of beans for storage is due to the decrease in culinary quality and the darkening of the seed coat. The objective of this work was to study the changes in the color of the testa and in the culinary quality promoted by the prolonged storage in two periods of time, in contrast to the change under accelerated aging in five varieties of beans. The color of the grain was quantified by reflectance spectrophotometry and the culinary quality by time and solids in the cooking broth. The accelerated aging caused “hardness to the baking”, but not hard test, on the contrary the prolonged storage at room temperature, although it did not promote hardness to the cooking, one of the five varieties showed hard testa. The darkening of the testa showed a positive correlation between all storage conditions. The correlation for L*between accelerated aging and that stored for four years was r= 0.84**, while the ratio of the first, with two years of storage, was r= 0.65*. These results indicate that the accelerated aging of the beans is an adequate method to select materials with less propensity to aging because it allows to anticipate the color change that could occur during prolonged storage.
Keywords: Phaseolus vulgaris L., accelerated and prolonged aging, cooking time, grain color.